Complete genome sequences and analysis of the Fusobacterium nucleatum subspecies animalis 7-1 bacteriophage ɸFunu1 and ɸFunu2. (April 2016) - Cochrane, Kyla; Manson McGuire, Abigail; Priest, Margaret E.; Abouelleil, Amr; Cerqueira, Gustavo C.; Lo, Reggie; Earl, Ashlee M.; Allen-Vercoe, Emma
Abstract: Fusobacterium nucleatum is a strictly anaerobic, Gram negative bacterial species that has been associated with dental infections, pre-term labor, appendicitis, inflammatory bowel disease, and, more recently, colorectal cancer. The species is unusual in its phenotypic and genotypic heterogeneity, with some strains demonstrating a more virulent phenotype than others; however, as yet the genetic basis for these differences is not understood. Bacteriophage are known to contribute to the virulence phenotype of several bacterial species. In this work, we set out to characterize the bacteriophage associated with F. nucleatum subsp. animalis strain 7-1, a highly invasive isolate from the human gastrointestinal tract. As well, we used computational approaches to predict and compare bacteriophage signatures across available sequenced F. nucleatum genomes. Highlights: Two new bacteriophage, ɸFunu1 and ɸFunu2, from a F.nucleatum strain, are reported. Bacteriophage were purified and characterized through genome sequencing and imaging. The bacteriophage are myoviridae with genome lengths of approximately 40, 000 bp. PHAST was assessed for prediction of bacteriophage within fusobacterial genomes.